2006
DOI: 10.1177/0091270006287932
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Maximum Drug Concentration and Area Under the Time‐Concentration Curve Between Humans and Animals for Oral and Intravenous Investigational Drugs

Abstract: The study compared maximum drug concentration (C(max)) and area under the time-concentration curve (AUC) after normalization of doses to body weight and to body surface area and developed relationships for C(max) and AUC between humans and animals for 75 oral and 10 intravenous investigational drugs. For the oral drugs, animal-human ratios of C(max) were different among animals in both normalizations. Surface area-normalized AUC ratios were not different, whereas weight-normalized ones were different. For both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Based on experience to date, the following distinction is suggested: (JMPR 2006(JMPR , 2007(JMPR , 2008JECFA 2011b) for some pesticide residues in food, such as the picolinic acid derivative, aminopyralid, the Nmethyl carbamate, carbofuran, some pyrethroids (cyfluthrin, cyhalothrin, and deltamethrin), and the mycotoxin, deoxynivalenol, illustrate principles relevant to both CSAF and categorical approaches. Adjustment factors of two-fold instead of the default TK subfactors were applied for both interspecies differences and human variability in TK, based principally on data from 75 pharmaceutical compounds (Fujita et al 2006) in which there was less variation in C max (which reflects less variable oral absorption) than in AUC (which reflects more variable clearance). Thus, the two-fold adjustment for these specific pesticides and food contaminants was related to class-specific (i.e.…”
Section: Terminology/definitionsmentioning
confidence: 99%
“…Based on experience to date, the following distinction is suggested: (JMPR 2006(JMPR , 2007(JMPR , 2008JECFA 2011b) for some pesticide residues in food, such as the picolinic acid derivative, aminopyralid, the Nmethyl carbamate, carbofuran, some pyrethroids (cyfluthrin, cyhalothrin, and deltamethrin), and the mycotoxin, deoxynivalenol, illustrate principles relevant to both CSAF and categorical approaches. Adjustment factors of two-fold instead of the default TK subfactors were applied for both interspecies differences and human variability in TK, based principally on data from 75 pharmaceutical compounds (Fujita et al 2006) in which there was less variation in C max (which reflects less variable oral absorption) than in AUC (which reflects more variable clearance). Thus, the two-fold adjustment for these specific pesticides and food contaminants was related to class-specific (i.e.…”
Section: Terminology/definitionsmentioning
confidence: 99%
“…Pharmacokinetic parameters were further calculated by dose and bodyweight normalization to evaluate the influence of gender. Specifically, as previous studies reported, 21,22 the dose and bodyweight normalized maximum plasma concentration ( C max,norm ) and area under the curve ( AUC 0‐t,norm and AUC inf,norm ) values were estimated by dividing by dose per kilogram of bodyweight. The dose and bodyweight normalized clearance ( CL norm ) and apparent volume of distribution ( Vd norm ) values were derived by dividing by the bodyweight.…”
Section: Methodsmentioning
confidence: 99%
“…Until now, only a few methods of transforming the values of PK parameters were proposed (Abdallah 1998; Fujita et al 2006). Frequently, these methods were based on data transformation through the normalization of pharmacokinetic parameters, value of the dose or physiological parameters (body weight, dose, body surface, normalization etc.…”
Section: Discussionmentioning
confidence: 99%